Acalypha Wilkesiana ‘Java White’: Identification of Some Bioactive Compounds by Gc-Ms and Their Effects on Key Enzymes Linked to Type 2 Diabete - Oyebode Olajumoke A.; Erukainure Ochuko L.; Koorbanally Neil A.; Islam Md. Shahidul (Acta Pharmaceutica)
In this study, we identified bioactive compounds from the ethanolic extracts of the leaves, stem bark and root bark of Acalypha wilkesiana through GC-MS analysis and investigated the effects of these extracts on some of the enzymes linked to type 2 diabetes. Plant parts were extracted sequentially with ethyl acetate, ethanol and water. GC-MS analysis revealed the presence of long-chain alkyl acids, esters, ketones and alcohols including phytol and phytol acetate along with some secondary metabolites such as xanthone, vitamin E and various types of sterols including stigmasterol, campesterol and sitosterol. Ethanolic extracts of all the parts showed a dose- -dependent inhibition of α-glucosidase and α-amylase activity. The extracts also demonstrated anti-lipase activity. The ethanolic extract of root bark showed the highest inhibition of enzymes compared to other extracts. The EC50 values (concentrations for 50 % inhibition) of α-glucosidase, α-amylase and lipase inhibition were 35.75 ± 1.95, 6.25 ± 1.05 and 101.33 ± 5.21 μg mL-1, resp. The study suggests that A. wilkesiana ethanolic extracts have the ability to inhibit the activity of enzymes linked to type 2 diabetes. Further studies are needed to confirm the responsible bioactive compounds in this regard.